(untitled) (UNIZIK Journal of Marketing, 2024)
This study investigates the impact of various collaboration strategies, proxy joint ventures, subcontracting, franchising, and outsourcing, on the performance of pharmaceutical companies in the region. The research employs a quantitative approach using a cross-sectional survey. The study sample comprises 370 top and middle executives of pharmaceuticals in southwest, Nigeria. The data were analyzed using a multiple regression analysis which revealed an R2 of .692., This indicates that collaboration strategy elements significantly contribute to increased innovation, cost efficiency, and market expansion. Nevertheless, the study also draws attention to difficulties with managing these collaboration efforts, including quality control problems, regulatory complications, and the requirement for robust policy frameworks. Businesses that effectively handle these obstacles by implementing a well-planned collaboration strategy typically see improvements in performance and a competitive advantage in the cutthroat industry. To spur innovation, save costs, and enhance overall performance, the study’s conclusion advises pharmaceutical companies in Lagos State to strategically diversify their cooperation efforts by incorporating joint ventures, subcontracting, franchising, and outsourcing into their business models. It also encourages legislators to expedite regulatory procedures and back programs that promote collaboration practices in the pharmaceutical industry. The study found that pharmaceutical performance in Lagos should be dependent on a collaboration strategy, which is the gap that the research attempted to address. The study therefore recommends that Pharmaceuticals in Lagos that seek improvement in profitability should adopt collaboration.